Blended anodes for lithium ion batteries

By using blended anode active materials in lithium-ion batteries, combined with the first and second anode active ingredients with different redox potentials, the capacity loss and life shortening caused by parasitic reactions between the anode and the electrolyte are solved, and the capacity loss and life shortening of the analytical reaction between the anode and the electrolyte are achieved. Higher energy density and longer battery life.

CN119481303APending Publication Date: 2025-02-18APPLE INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411084721.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-11
Filing Date
2024-08-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When existing lithium-ion batteries operate at high voltages, parasitic reactions between the anode active material and the electrolyte accelerate, resulting in irreversible capacity loss and shortened battery life.

Method used

Using a blended anode active material, which includes a first anode active component and a second anode active component with different redox potentials, improves the energy density and lifetime of the battery by tuning the electrochemical window of the cathode.

Benefits of technology

By blending the anode active material, the shift of the anode potential is reduced, cathode deterioration and electrolyte consumption are reduced, and the cycle life and calendar life of the battery are extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481303A_ABST
    Figure CN119481303A_ABST
Patent Text Reader

Abstract

The present disclosure provides a blended anode for a lithium ion battery. The present disclosure relates to a blended anode material comprising at least two types of electrochemically active components having different redox potentials. The anode design imparts a number of advantageous characteristics that provide chemical and structural stability over conventional single-phase graphite anodes, particularly at high and / or low electrochemical potentials.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Priority claim

[0002] This application claims the benefit of priority to U.S. Provisional Application No. 63 / 519,192, filed on August 11, 2023, the disclosure of which is hereby incorporated by reference in its entirety. Technical Field

[0003] The present disclosure relates generally to batteries, and more particularly to anode active materials for lithium-ion batteries. Background Art

[0004] High-performance lithium-ion batteries are used to address growing energy demands and environmental challenges.

[0005] Energy density, one of the main characteristics of a battery, is a function of the deliverable capacity and the operating voltage. Improving energy density can generally include (1) maximizing the electrochemical potential difference between the cathode and the anode (i.e., raising the upper cutoff voltage (Vmax) to which the battery can be charged), (2) increasing the electrochemical stability window of the electrolyte components to limit harmful reduction and oxidation reactions of the liquid electrolyte and salts; and (3) reducing the mass and volume of active materials per exchange of electrons.

[0006] Layered lithium transition metal oxides (Li x M y O z , M = transition metal element, such as Ni, Mn, Co...) generally have a compact structure and therefore have high packing density, high volumetric capacity, stable charge / discharge voltage and relatively good cyclability. Improvements in batteries operating at high voltages are particularly desirable. Summary of the invention

[0007] In one aspect, the present disclosure relates to a battery cell comprising a cathode having a cathode active material disposed on a cathode current collector; and an anode comprising a blended anode active material disposed on an anode current collector. The blended anode active material comprises a first anode active component and a second anode active component having a lower redox potential than the first anode active component.

[0008] In some variations, the anode has a lower anode potential than a single-phase anode having only the first anode active component and not the second anode active component.

[0009] In some variations, the battery cell has less electrolyte degradation as a function of cycle count or calendar life compared to a battery cell including only the first anode active component and not the second anode active component.

[0010] In some variations, the battery cell has less solid electrolyte interphase (SEI) degradation as a function of cycle count compared to a battery cell including only the first anode active component and not the second anode active component.

[0011] In some variations, the cathode has a lower potential than a cathode in a battery cell including an anode that includes only the first anode active ingredient and not the second anode active ingredient.

[0012] In some variations, the cathode active material has less degradation as a function of cycle count or calendar life compared to a battery cell including only the first anode active component and not the second anode active component.

[0013] In the second aspect, the amounts of the first anode component and the second anode component can be different amounts. In one variation, the mass ratio of the second anode active component to the first anode active component is in the range of 1:200 to 200:1.

[0014] In some variations, the first anode active component is selected from graphite and an intermetallic alloy-based material. In further variations, the intermetallic alloy-based material is selected from silicon, tin, lithium silicon alloys, and lithium tin alloys. In still further variations, the first anode component is graphite. In still further variations, the first anode active component is an ordered matrix.

[0015] In some variations, the second anode active ingredient is selected from disordered graphitic carbon, non-graphitic carbon, and nanostructured carbon materials. In further variations, the second anode active ingredient is non-graphitic carbon selected from hard carbon and microporous / mesoporous carbon. In further variations, the second anode active ingredient is hard carbon. In additional variations, the nanostructured carbon material is selected from carbon nanotubes, graphene sheets, and reduced graphene oxide.

[0016] In some variations, the cathode current collector is an aluminum foil. In additional variations, the anode current collector is a copper foil.

[0017] In some variations, the cathode active material is a lithium transition metal oxide. In further variations, the lithium transition metal oxide is a compound of formula (I):

[0018] Li a Co 1-b Me b O c (I)

[0019] wherein

[0020] Me is selected from Na, Si, S, Al, K, V, Cr, Fe, Cu, Zn, Mn, Ni, Zr, La, Ce, Y, Mo, Sn, Ag, Nb, Nu, Ca, Ti, Mg, and combinations thereof;

[0021] 0.95 ≤ a ≤ 1.05;

[0022] 0 < b ≤ 0.50; and

[0023] 1.95c ≤ 2.05.

[0024] In some variations, when Me is a single element selected from Na, Si, S, Al, K, V, Cr, Fe, Cu, Zn, Mn, Ni, Zr, La, Ce, Y, Mo, Sn, Ag, Nb, Nu, Ca, Ti, and Mg, then 0 < b ≤ 0.15. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present disclosure will be readily understood by the following detailed description in conjunction with the accompanying drawings, where like reference numerals denote like structural elements, and in the drawings:

[0026] Figure 1 is a top view of a battery cell according to an exemplary embodiment;

[0027] Figure 2 is a side view of a set of layers of a battery cell according to an exemplary embodiment;

[0028] Figure 3A depicts the potential distributions of the cathode and anode during a charge cycle, and the corresponding full cell voltage distribution, according to an exemplary embodiment;

[0029] Figure 3B depicts the relative shift in the potential distributions of the cathode and single-phase anode before and after cycling, and the corresponding full cell voltage distribution near the end of charge, according to an exemplary embodiment;

[0030] Figure 3C depicts the relative shift in the potential distributions of the cathode and blended anode before and after cycling, and the corresponding full cell voltage distribution near the end of charge, according to an exemplary embodiment;

[0031] Figure 4Adepicts an electrochemical potential of a single-phase anode coupled to a cathode compared to a blended anode coupled to the cathode according to an exemplary embodiment;

[0032] Figure 4B depicts the effect of an anode potential on a corresponding cathode potential according to an exemplary embodiment;

[0033] Figure 5A depicts the low voltage effect of a single phase anode compared to a blended anode according to an exemplary embodiment;

[0034] Figure 5B depicts a shift in lower cutoff potential for a single phase anode compared to a blended anode according to an exemplary embodiment; and

[0035] Figure 6 Depicted is 0.2C energy retention normalized to the minimum rated design value for a cell having a control anode containing 100% graphite and a cell having an anode design containing 1% hard carbon blended with the control graphite cycled at 45°C according to an exemplary embodiment. DETAILED DESCRIPTION

[0036] The following description is given to allow any technician in the field to make and use the embodiments, and the following description is provided in the context of a specific application. For those skilled in the art, various modifications to the embodiments disclosed by the present invention will be apparent, and the general principles defined herein can be applied to other embodiments and applications without departing from the essence and scope of the present disclosure. It should be understood that the following description is not intended to limit the embodiments to a preferred embodiment. On the contrary, it is intended to cover substitutions, modifications and equivalents that may be included in the essence and scope of the described embodiments defined by the appended claims. Therefore, the present disclosure is not limited to the embodiments shown, but is in accordance with the broadest scope of the principles and features disclosed herein.

[0037] As used herein, unless otherwise indicated, all compositions for cathode active materials represent compositions of prepared materials (i.e., "raw" materials). The materials of these compositions have not been exposed to additional processes, such as delithiation and lithiation during charging and discharging of lithium-ion batteries, respectively.

[0038] The present disclosure relates to a blended anode active material comprising at least two types of electrochemically active components with different redox potentials. The blended anode design incorporating the blended anode active material can impart many advantageous properties to the battery. This includes improved chemical and structural stability compared to conventional single-phase graphite anodes, particularly at high and / or low electrochemical potentials. When coupled to a cathode, the first anode component and the second anode component are selected based on the redox potential difference of the first anode component and the second anode component to tune the electrochemical window of the cathode. Such selection or tuning can improve the energy density and / or life of the battery compared to conventional single-phase anode batteries.

[0039] Figure 1 A top view of a battery cell 100 according to one embodiment is shown. The battery cell 100 may correspond to a lithium ion or lithium polymer battery cell for powering devices used in consumer, medical, aviation, defense, and / or transportation applications. The battery cell 100 includes a stack 102 comprising a plurality of layers including a cathode, a separator, and an anode. The stack 102 also includes a separator disposed between the cathode and the anode. The cathode, anode, and separator layers may remain flat in a planar configuration or may be wound into a wound configuration (e.g., a "jelly roll").

[0040] The battery cell may be enclosed in a flexible bag or a hard case, for example. Figure 1 , during the assembly of the battery cell 100, the stack 102 may be enclosed in a bag. The bag may be flexible or rigid. The stack 102 may be in a planar or wound configuration, but other configurations are also possible. If flexible, the bag may be formed by folding a flexible sheet along a fold line 112. For example, the flexible sheet may be made of aluminum with a polymer film (such as polypropylene). After folding the flexible sheet, the flexible sheet may be sealed, for example, by applying heat along the side seals 110 and along the platform seals 108. In some variations, the thickness of the flexible bag may be less than 120 microns to improve the packaging efficiency of the battery cell 100, the density of the battery cell 100, or both.

[0041] The stack 102 also includes a set of conductive tabs 106 coupled to the cathode and anode. The conductive tabs 106 may extend through a seal in the bag (e.g., a seal formed using the sealing tape 104) to provide terminals for the battery cell 100. The conductive tabs 106 may then be used to electrically couple the battery cell 100 with one or more other battery cells to form a battery pack.

[0042] The batteries may be combined in a battery pack of any configuration. For example, a battery pack may be formed by coupling battery cells in series, parallel, or in a series-parallel configuration. Such coupled cells may be enclosed in a hard case to complete the battery pack, or may be embedded within the housing of a portable electronic device such as a laptop computer, tablet computer, mobile phone, personal digital assistant (PDA), digital camera, and / or portable media player.

[0043] Figure 2 A battery cell (eg, Figure 1 1. A side view of a set of layers of a battery cell 100 of FIG. 1. The set of layers may include a cathode current collector 202, a cathode active material 204, a separator 206, an anode active material 208, and an anode current collector 210. The cathode current collector 202 and the cathode active material 204 form the cathode of the battery cell, and the anode current collector 210 and the anode active material 208 form the anode of the battery cell. To form a battery cell, the set of layers may be stacked in a planar configuration, or stacked and then wound into a wound configuration.

[0044] As described above, cathode current collector 202 may be an aluminum foil, cathode active material 204 may be a lithium transition metal oxide compound, anode current collector 210 may be a copper foil, and separator 206 may include a conductive polymer electrolyte.

[0045] It should be understood that the cathode active materials described herein can be used in conjunction with any battery cell or component thereof known in the art. For example, in addition to wound battery cells, the layers can be stacked and / or used to form other types of battery cell structures, such as a dual-cell structure. All such battery cell structures are known in the art.

[0046] In higher voltage applications, the lifetime of full-cells is fundamentally challenged by the metastable nature of electrochemical processes. On the one hand, the cathode active materials undergo irreversible structural changes due to fatigue cycles of lattice strain generated during Li-ion insertion / deinsertion and stronger parasitic reactions between the cathode surface and the electrolyte. On the other hand, parasitic reactions between the anode active materials and the electrolyte are also accelerated as the anode is charged to lower electrochemical potentials, which consumes Li ions available for charge / discharge and leads to irreversible capacity loss.

[0047] Any cathode active material known in the art can be used in the compositions, cells, and methods described herein.

[0048] In some variations, the cathode active material is a layered lithium transition metal oxide (Li x M y O z, M = transition metal element, such as Ni, Mn, Co...). The layered lithium transition metal oxide may have a compact structure and thus has a high packing density, a high volumetric specific capacity, a stable charge / discharge voltage, and relatively good recyclability.

[0049] In some further variants, the cathode active material comprises a compound represented by formula (I):

[0050] Li a Co 1-b Me b O c (I)

[0051] wherein

[0052] Me is selected from Na, Si, S, Al, K, V, Cr, Fe, Cu, Zn, Mn, Ni, Zr, La, Ce, Y, Mo, Sn, Ag, Nb, Nu, Ca, Ti, Mg, and combinations thereof;

[0053] 0.95 ≤ a ≤ 1.05;

[0054] 0 < b ≤ 0.50; and

[0055] 1.95 ≤ c ≤ 2.05.

[0056] In some variants, in the case where Me is a single element selected from Na, Si, S, Al, K, V, Cr, Fe, Cu, Zn, Mn, Ni, Zr, La, Ce, Y, Mo, Sn, Ag, Nb, Nu, Ca, Ti, and Mg, then 0 < b ≤ 0.15.

[0057] In a further variant, Me is more than one element and each individual element present in b is less than or equal to 0.10.

[0058] In a still further variant, Me is selected from Al, Mn, Ni, Zr, La, Ce, Y, Mo, Sn, Ag, Nb, Ca, Ti, and Mg. The amount of any one or more elements of Me or the selected group of Me can be combined with the amount of each one or more elements in any combination described herein.

[0059] The compound can be any compound described in PCT US2017 / 052436 or PCT / US2017 / 022320, the entire texts of which are incorporated herein by reference.

[0060] The present disclosure relates to a blended anode active material comprising at least a first anode active component and a second anode active component having different redox potentials.

[0061] The blended anode can impart one or more advantages to the battery cell. The blended anode can impart improved chemical and structural stability to conventional single-phase anodes (e.g., graphite anodes), particularly at high and / or low electrochemical potentials. The components of the blended anode active materials can have different electrochemical redox potentials and can be charged / discharged separately according to their specific redox potentials. When coupled with a cathode system, the blended anode can be used to tune the electrochemical window of the cathode to improve energy density and / or life compared to conventional single-phase anode batteries.

[0062] The blended anode active material includes at least two types of active ingredients. Generally speaking, the first anode active ingredient has a higher anode potential than the second anode active ingredient. In some variations, the first anode ingredient can be graphite or an intermetallic alloy-based material. Examples of intermetallic alloy-based materials can be silicon, tin, lithium silicon alloys, lithium tin alloys. In variations, the first anode active ingredient acts as an ordered "matrix" in which the second anode active ingredient can be placed. In some variations, the first anode ingredient is graphite.

[0063] The blended anode active material includes a second anode active ingredient that exhibits a redox potential lower than that of the first anode active ingredient. In a variation, the second anode active ingredient may be selected from disordered graphite carbon, non-graphite carbon, and nanostructured carbon materials. Non-limiting examples of non-graphite carbon include hard carbon or other microporous / mesoporous carbons. Non-limiting examples of nanostructured carbon materials include carbon nanotubes, graphene sheets, and reduced graphene oxides. In some variations, the second anode active material is hard carbon. The second anode active ingredient may be considered an "additive". In various aspects, the included second anode active ingredient has different crystallinity (e.g., smaller-sized graphite domains or larger interlayer distances) relative to graphite, and may be considered "disordered" compared to the first cathode active ingredient.

[0064] In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is in a range from 1:200 to 200:1.

[0065] In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 1:200. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 1:180. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 1:160. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 1:140. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 1:120. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 1:100. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 1:80. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 1:60. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 1:40. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 1:20. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 1:1.

[0066] In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 20:1. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 40:1. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 60:1. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 80:1. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 100:1. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 120:1. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 140:1. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 160:1. In some variations, the mass ratio of the first anode active ingredient to the second anode active ingredient is greater than or equal to 180:1.

[0067] In some variations, the mass ratio of the first anode to the second anode is less than or equal to 200:1. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 180:1. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 160:1. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 140:1. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 120:1. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 100:1. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 80:1. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 60:1. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 40:1. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 20:1. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 1:1.

[0068] In some variations, the mass ratio of the first anode to the second anode is less than or equal to 1:20. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 1:40. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 1:60. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 1:80. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 1:100. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 1:120. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 1:140. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 1:160. In some variations, the mass ratio of the first anode to the second anode is less than or equal to 1:180.

[0069] The upper and lower limits of the mass ratio of the first anode to the second anode may be selected in any combination. For example, in some non-limiting examples of graphite and hard carbon blended anodes, the mass ratio of hard carbon to graphite is generally in the range of 1:200 to 1:1.

[0070] In conventional single-phase graphite anodes, irreversible capacity loss due to depletion of Li ion inventory at the anode can cause its potential profile to shift relative to the cathode potential profile. This shift is reduced in blended anodes.

[0071] Figure 3A The relative shift in the electrode potential profiles of cathode 302 and anode 304 during a charge cycle 306 is depicted, along with the corresponding full cell voltage profile. Figure 3B, depicts the potential distribution as a function of the state of charge (SoC) of the transition metal cathode 302a and the graphite anode 304a at the end of charging when the full cell voltage approaches Vmax 308a, together with the full cell voltage 306a. Vmax 308a refers to the upper cut-off voltage. As Li ions and electrons are irreversibly consumed at the anode, the anode SoC 304a gradually decreases, accompanied by an increase in the anode potential at the end of charging. In order to compensate for the Li ion and electron losses and keep Vmax 308a constant, additional cathode capacity is obtained, which produces a simultaneous increase in cathode potential 302a. The increase in cathode potential 302a causes the cathode to be "overcharged" during cycling. The "tilted" potential distribution of both cathode 302a and anode 304a leads to degradation of the cathode and oxidation of the electrolyte at the cathode surface.

[0072] The lifetime of the cell for low voltage discharge is limited by the stability of the anode / electrolyte interface. Figure 3A , near the end of discharge, when all Li ions are extracted from the graphite anode active material, the full cell voltage distribution becomes steeply sloped as the anode polarizes to a high potential. The solid electrolyte interphase (SEI) (not shown) formed on the anode is prone to mechanical cracking caused by anode shrinkage at lower SoC. The re-exposed anode surface can promote further electrolyte decomposition, which also depletes the Li ion inventory within the cycle and shortens the life of the battery.

[0073] Further references Figure 3B , the potential profiles of the cathode 302a and anode 304a and the corresponding full cell voltage 306a profile during a charge cycle. The anode potential curve 304a shifts to the right. The cathode potential curve 302a also increases to keep the full cell voltage 306a at a constant Vmax 308a. The increase in cathode potential results in more cathode capacity being obtained and thus cathode degradation.

[0074] Figure 3C The relative shifts of the potential profiles of the cathode 302b and the blended anode 304b before and after cycling are depicted. The anode potential curve 304b shifts to the right, while the anode potential at the end of charge remains unchanged due to the additional lower potential plateau. The cathode potential curve 302b thus maintains the same shape and does not shift upward to maintain the full cell voltage 306b at a constant Vmax 308b.

[0075] The higher the cathode potential, the faster cathode degradation occurs. In addition, electrolyte consumption is accelerated, reducing the SEI at the anode. If the cathode potential is at a lower value at the same cell voltage, cathode degradation and electrolyte consumption occur more slowly, resulting in a longer battery life.

[0076] Figure 4ADepicted is the electrochemical potential of a single-phase anode 402a coupled to a cathode 404a compared to a blended anode 402b coupled to a cathode 404b.

[0077] Figure 4B The net effect on the anode potential (402a, 402b) and the corresponding cathode potential (404a, 404b) near the end of charging is depicted. Vmax (406a, 406b) is fixed in both the single-phase anode potential 402a and the blended anode potential 402b. The battery is charged to a state of charge 408 where the battery cell is fully charged. The blended anode potential decreases to near zero. With constant Vmax (406a, 406b), the blended anode potential 402b has a lower potential than the single-phase anode potential 402a, resulting in a lower cathode potential 404b compared to 404a.

[0078] The second anode component (e.g., hard carbon) has a lower redox potential than graphite. In addition, unlike pure graphite, lithium is not easily plated in a disordered second anode component such as hard carbon. The lower plateau capacity of the second anode component results in a simultaneously reduced anode and cathode potential relative to a single-phase graphite anode design. This improves the life cycle of the battery cell.

[0079] By way of example and not limitation, if the first anode component is graphite and the second anode component is hard carbon, then when the graphite phase transition is completed (LiC 12 To LiC6), the lithiation of graphite is usually at 50mV-85mV (relative to Li / Li + ) shows a potential plateau. Overlithiation of graphite beyond this dual-phase region induces lithium-metal nucleation reactions and strong electrolyte reduction. In contrast, hard carbon has a potential plateau at about 0 V (vs. Li / Li + ) exhibits a long-range plateau capacity, which is attributed to the formation of lithium nanoclusters in the inner pores of hard carbon. Therefore, this difference in the anode potential close to the fully charged state shifts the cathode potential by 50mV-85mV, which effectively reduces the cathode SoC.

[0080] From a dynamic point of view, the risk of cathode overcharging during repeated charging and discharging is also mitigated by implementing a blended anode. When a sufficient amount of a second anode component (such as hard carbon) is blended into a first anode component (e.g., graphite), the anode remains in a "flat" potential state at the end of charging, even when Li ion inventory loss occurs. This allows the cathode potential to remain unchanged during over-cycling, such as Figure 3C As shown, this alleviates the cathode degradation which is aggravated by the upward shift of the cathode potential.

[0081] In contrast to single-phase anodes, blended anodes also benefit low-voltage applications by changing the electrode potential profile near the end of discharge. Figure 5AAs shown, the capacity of the full cell with a single-phase anode 502a is largely limited by the anode capacity, which is mainly due to the more steep rise in the potential profile of the anode compared to the potential profile of the cathode 504a. As the anode potential rises rapidly, the graphite undergoes non-uniform volume changes and SEI dissolution. This results in more lithium consumption on the anode side, which adversely affects stability. In contrast, the capacity of the full cell using a blended anode 502b may be more limited by the cathode 504b because the Li ions in the blended anode 502b are less rapidly depleted. Relative Figure 5B , which is manifested by the simultaneous reduction of the anode and cathode potentials at the end of discharge to keep the full cell voltage constant (i.e., a constant lower cutoff voltage 506b compared to 506a). SEI degradation caused by volume changes of the "deeply discharged" anode is thus effectively circumvented. When the anode potential profile is shifted to the right due to the loss of Li ion inventory, the increase in the anode end-of-discharge potential is less harmful because of the delayed Li ion depletion of the blended anode.

[0082] Figure 6 The 0.2C energy retention normalized to the minimum rated design value is shown for cells with a control anode containing 100% graphite and cells with an anode design containing 1% hard carbon blended with the control graphite cycled at 45°C. The energy retention shows significantly better results at 250 cycles, an improvement of 5% over the baseline, and overcomes the rapid energy decay behavior of the cell at the high operating voltage of 4.52V.

[0083] The anodes, battery cells, and other materials described herein can be valuable in any battery-containing device, including those used in electronic devices and consumer electronics. An electronic device herein can refer to any electronic device known in the art. For example, an electronic device can be a telephone such as a mobile phone and a landline phone, or any communication device such as a smart phone (including, for example, ), and email sending / receiving devices. The electronic device may also be an entertainment device, including a portable DVD player, a conventional DVD player, a Blu-ray player, a video game controller, a music player such as a portable music player (e.g., ). The electronic device may be part of a display such as a digital display, a television monitor, an e-book reader, a portable web browser (e.g., ), a watch (e.g., Apple Watch), or a computer monitor. The electronic device may also be part of a device that provides control, such as controlling the flow of images, video, sound (e.g., Apple ), or it may be a remote control for an electronic device. In addition, the electronic device may be a part of a computer or its accessories, such as a hard drive tower housing or protective case, a laptop housing, a laptop keyboard, a laptop trackpad, a desktop computer keyboard, a mouse, and a speaker. The anode unit, lithium metal battery, and battery pack may also be applied to devices such as watches or clocks.

[0084] For the purpose of illustration, the foregoing description uses specific nomenclature to provide a thorough understanding of the embodiments. However, it will be apparent to those skilled in the art that specific details are not required in order to practice the embodiments. Therefore, for the purpose of illustration and description, the foregoing description of the specific embodiments described herein is presented. They are not intended to be exhaustive or to limit the embodiments to the disclosed precise forms. It will be apparent to those of ordinary skill in the art that, in view of the above teachings, many modifications and variations are feasible.

Claims

1. A battery cell, comprising: cathode and anode; The cathode includes a cathode active material disposed on a cathode current collector; and The anode includes a blended anode active material disposed on an anode current collector; The blended anode active material includes a first anode active ingredient and a second anode active ingredient having a lower redox potential than the first anode active ingredient. 2 . The battery cell according to claim 1 , wherein the anode has a lower potential than a single-phase anode consisting only of the first anode active component.

3. The battery cell of claim 1, wherein the battery cell has less electrolyte degradation as a function of cycle count or calendar life compared to a battery including an anode consisting solely of the first anode active component.

4. The battery cell of claim 1, wherein the battery cell has less solid electrolyte interphase (SEI) degradation as a function of cycle count compared to a battery including an anode consisting only of the first anode active component.

5. The battery cell according to one of claims 2 to 4, wherein the cathode has a lower potential than a cathode in a battery comprising an anode consisting only of the first anode active ingredient.

6. The battery cell of claim 5, wherein the cathode active material has less degradation as a function of cycle count or calendar life compared to the battery including an anode consisting solely of the first anode active component.

7. The battery cell of any preceding claim, wherein the ratio of the mass of the first anode active component to the mass of the second anode active component is from 1:200 to 200:

1.

8. The battery cell according to claim 7, wherein the first anode active ingredient is graphite, and the second anode active ingredient is hard carbon, and The mass ratio of the first anode active component to the second anode active component is 1:200 to 1:

1.

9. The battery cell of any preceding claim, wherein the first anode active component is selected from graphite and intermetallic alloy based materials.

10. The battery cell of claim 9, wherein the first anode active component is an intermetallic alloy-based material selected from the group consisting of silicon, tin, lithium silicon alloy, and lithium tin alloy.

11. The battery cell of claim 9, wherein the first anode component is graphite.

12. The battery cell of any preceding claim, wherein the first anode active component is an ordered matrix.

13. The battery cell of any preceding claim, wherein the second anode active component is selected from the group consisting of disordered graphitic carbon, non-graphitic carbon, and nanostructured carbon materials.

14. The battery cell of claim 13, wherein the second anode active component is a non-graphite carbon selected from hard carbon and microporous / mesoporous carbon.

15. The battery cell of claim 14, wherein the second anode active ingredient is hard carbon.

16. The battery cell according to claim 13, wherein the second anode active ingredient is a nanostructured carbon material selected from carbon nanotubes, graphene sheets, and reduced graphene oxide.

17. The battery cell according to any one of the preceding claims, wherein the cathode current collector is aluminum foil.

18. The battery cell according to any one of the preceding claims, wherein the anode current collector is copper foil.

19. The battery cell according to any one of the preceding claims, wherein the cathode active material comprises a lithium transition metal oxide.

20. The battery cell according to claim 19, wherein the lithium transition metal oxide is a compound of formula (I): Li a Co 1-b Along with b O c (I) wherein Me is selected from Na, Si, S, Al, K, V, Cr, Fe, Cu, Zn, Mn, Ni, Zr, La, Ce, Y, Mo, Sn, Ag, Nb, Nu, Ca, Ti, Mg, and combinations thereof; 0.95≤a≤1.05; 0 < b ≤ 0.50; and 1.95≤c≤2.05。 21. The battery cell according to claim 20, wherein Me is a single element selected from Na, Si, S, Al, K, V, Cr, Fe, Cu, Zn, Mn, Ni, Zr, La, Ce, Y, Mo, Sn, Ag, Nb, Nu, Ca, Ti, and Mg, then 0 < b ≤ 0.15.

Citation Information

Patent Citations

  • Front-end lighting system for projection and projection device

    US20170052436A1